Meta-Analysis: Effectiveness of Scoliosis Brace to Reduce Scoliosis Curve Degree in Adolescent Idiopathic Scoliosis - Etanaulia Marsim; Hanung Prasetya; Bhisma Murti (Indonesian Journal of Medicine, 2023)
Background: Adolescent Idiopathic Scoliosis (AIS) is a disorder of the spine that is curved laterally which includes rotation of the spine so that there is humpback on the ribs, which occurs in children aged 10-18 years. The use of a brace is an attempt to modify the mechanical shape and control the development of curves in the curvature of the spine by applying certain pressure points on the body. The purpose of this study was to determine the magnitude of the effect of using the scoliosis brace to reduce the degree of scoliosis in adolescents with idiopathic scoliosis.Subjects and Method: This study was conducted using a systematic review and meta-analysis study design using PICO, population: adolescent idiopathic scoliosis, intervention: using a scoliosis brace. comparison: not using a scoliosis brace, outcome: degree of scoliosis. The articles used in this study come from 3 databases, namely Google Scholar, PubMed, and Science Direct. With keywords including "Adolescent scoliosis" OR "scoliosis" AND "scoliosis brace" OR "brace" AND "degree of scoliosis" OR "Cobb Angle" AND "randomized control trial". The articles included in this study are full paper articles with experimental studies, research subjects of adolescent patients with scoliosis, articles published in the 2011-2021 period.Results: A meta-analysis was conducted on 10 primary randomized control trials conducted from Turkey, China, Canada, Switzerland, the United States, and Hong Kong, with a total sample size of 558. The meta-analysis concluded that adolescent patients with idiopathic scoliosis who received intervention The scoliosis brace had a lower grade of scoliosis 0.27 compared to adolescents who did not use the scoliosis brace, and the difference was statistically significant (SMD= -0.27; 95% CI= -0.45 to –0.09; p= 0.003).Conclusion: The use of a scoliosis brace can reduce the degree of scoliosis in adolescents with idiopathic scoliosis.Keywords: adolescent idiopathic scoliosis, scoliosis brace, cobb angleCorespondence: Etanaulia Marsim. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: etanaulia@gmail.com. Mobile: +6285840530580.Indonesian Journal of Medicine (2023), 08(01): 12-22https://doi.org/10.26911/theijmed.2023.08.01.02